2017
DOI: 10.1515/hsz-2016-0280
|View full text |Cite
|
Sign up to set email alerts
|

β-NGF and β-NGF receptor upregulation in blood and synovial fluid in osteoarthritis

Abstract: Osteoarthritis (OA) of the knee is the most common form of non-traumatic joint disease. Previous studies have shown the involvement of β-NGF and its receptors TrKA and p75NTR in OA-related pain, but their role in its pathogenesis is still unclear. The aim of our study was to investigate the amount of β-NGF and the expression levels of its receptors on cells isolated from synovial fluid and blood from OA patients who had undergone total knee arthroplasty, in order to check any possible correlation with the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…Increased NGF levels have been reported in inflammatory conditions such as rheumatoid arthritis, spondyloarthritis, and osteoarthritis . We previously evaluated Ngf mRNA expression in the acute phase of injury and revealed that expression was increased 1 day after disc injury in mice, as was also observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Increased NGF levels have been reported in inflammatory conditions such as rheumatoid arthritis, spondyloarthritis, and osteoarthritis . We previously evaluated Ngf mRNA expression in the acute phase of injury and revealed that expression was increased 1 day after disc injury in mice, as was also observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“… 40 Thus, NGF concentrations are increased in chronic pain conditions such as interstitial cystitis, prostatitis, arthritis, pancreatitis, chronic headaches, cancer pain, diabetic neuropathy, and noncancer pain, suggesting that NGF-mediated signaling is an ongoing and active process in chronic nociceptive and neuropathic pain states. 12 , 41 51 Given the evidence that NGF plays an important role in driving skeletal pain, one important data set that we still do not have is what specific sets of cells in the intact bone express NGF, TrkA, or p75. 4 , 32 , 33 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was assessed that dysregulated production of NGF determines proliferation of synovial cells influencing the inflammatory and proliferative cascades typical of inflammatory arthritis [110]. More recently, in accordance with Stoppiello et al who assessed increased synovial NGF in synovitis [115], Montagnoli et al confirmed a stage-related increase of β -NGF and its receptors in the inflammatory process of OA both in serum and synovial fluid [116].…”
Section: Ifp-synovial Membrane Mediators Involved In Oa Pathologymentioning
confidence: 95%